Novel uricosurics. (19th December 2017) - Bardin, Thomas; Richette, Pascal
Abstract: Objective: According to recent guidelines, the mainstay of urate-lowering therapies remains xanthine oxidase inhibition. However, some patients with gout show failure to achieve the predefined target of 5–6 mg/dl with xanthine oxidase inhibitors alone, so alternative drugs are needed. The aim of this study was to review studies of novel drugs targeting uric acid transporter 1 (URAT1) and/or other urate transporters for the management of gout. Methods: MeSH terms were used to identify phase 2/3 trials assessing the efficacy of novel uricosurics. A narrative review of novel drugs targeting URAT1 and/or other urate transporters for the management of gout is provided. Results: Lesinurad is a recently approved uricosuric that inhibits URAT1 and the organic ion transporter organic anion transporter 4 (OAT4). Phase 3 trials showed that lesinurad, combined with allopurinol or febuxostat, is a potent urate-lowering therapeutic with an acceptable safety profile. Arhalofenate, another emerging uricosuric, also interacts with URAT1 and organic anion transporter 4. Phase 2 trials suggested that it can both lower serum UA levels and reduce the risk of flares. Conclusions: New drugs inhibiting URAT1 should cover the unmet need for patients with failure to respond or with contraindications to xanthine oxidase inhibitors.